Natural resource tenure and governance for human nutrition and health: Linkages and priorities for agricultural research and development - Johnson, Nancy L. (International Food Policy Research Institute, 2021)
Rapid transformations are occurring in food systems around the world with significant economic, health, and environmental implications. As part of this change, the focus of agricultural production needs to transition from quantity of food production to quality of diets. This brief begins by summarizing evidence from nutrition-sensitive agriculture and explaining how resource tenure and governance issues relate to the production of nutrient-rich foods. The brief then explores the importance of resource tenure and governance issues for diets and health in the context of food system transformation: this section focuses on supporting healthy diets in traditional food systems, meeting the global demand for nutrient-rich foods, and managing and mitigating disease risks in intensifying agricultural landscapes.